Assessing land clearing potential in the Canadian agriculture–forestry interface with a multi-attribute frontier approach. (July 2015) - Yemshanov, Denys; Koch, Frank H.; Riitters, Kurt H.; McConkey, Brian; Huffman, Ted; Smith, Stephen
Highlights: We develop a new single-dimensional metric of land clearing potential. The new land clearing metric is based on a multi-attribute frontier principle. The metric considers the trade-off between the land's production and fragmentation potential. We assess the land clearing pressures in the Canadian agriculture–forestry interface. Our geographical estimates agree with recent evidence of land clearing events in Canada. Abstract: The pattern of forest land clearing in a region can be viewed as a gauge of sustainable (or unsustainable) use of agricultural and forest resources. In this study we examine the geographical distribution of land clearing potential in the Canadian agriculture–forestry interface and propose a new landscape-scale indicator that quantifies this potential. We consider the possibility that forested land will be cleared for agriculture as a trade-off between the land's capacity to support agriculture and its comparative value if it remains forested. However, this trade-off is complicated by the land's susceptibility to fragmentation (and subsequent conversion), which derives from the local pattern of forest, agriculture and other land cover types. We find the locations in the agriculture–forestry interface with the highest land clearing potential by delineating nested multi-attribute frontiers in the dimensions of the land's agricultural capacity, its estimated forest productivity and its fragmentation potential. The multi-attribute frontier concept addresses our lack of knowledge about the relative importance of these multiple drivers of land conversion by objectively combining them into a single-dimensional land clearing pressure metric in a geographical setting. Overall, our approach provides a simple yet informative indicator which reveals the geographical stratification of land clearing pressures across large regions. In general, the spatial delineation of areas with high land clearing potential agrees well with recent evidence of land clearing and deforestation events in Canada.